Functional resilience: An active oxidative phosphorylation system prevails amid foreign proteins in holoparasitic plants - Gatica Soria, Leonardo Martin (2024)
Mitonuclear incompatibility results from a breakdown of the coordinated function between co-evolved genes located in nuclear and mitochondrial compartments. Horizontal Gene Transfer (HGT), involving the acquisition of genes from unrelated species, can trigger mitonuclear incompatibilities when foreign gene products interact with native ones, particularly in multisubunit complexes. Recent findings highlighted rampant HGT in the mitochondrial genomes of holoparasitic plants of the genus Lophophytum (Balanophoraceae). In Lophophytum, some mitochondrial genes involved in the Oxidative Phosphorylation (OXPHOS) system were acquired from their legume hosts, unlike the nuclear-encoded OXPHOS subunits, which remain native. This unique configuration of a doubly chimeric OXPHOS, combining native nuclear-encoded subunits with both foreign and native mitochondrial-encoded subunits, raises questions regarding the potential effects of the interactions between native and foreign proteins on mitochondrial respiration activity in Lophophytum. We examined the mitochondrial ultrastructure, evaluated protein expression via Western blots, and analyzed cellular respiration through oxygen consumption rates and adenylate content in these holoparasitic plants. Surprisingly, our results revealed no disruption of the OXPHOS machinery or activity in Lophophytum despite the functional replacement of several native protein subunits by foreign homologs. Furthermore, there was no apparent impact on the OXPHOS system given their parasitic lifestyle and complete loss of photosynthesis.